Performance Of Commercial Strains Chicken Given Commercial Based Feed - D R Siregar; E Mirwandhono; AH Daulay; N D Hanafi; T H Wahyuni (Talenta Publisher, 2018)
This research aimed to conclude the best combination of commercial strain and feed on broiler’s carcass. This research was conducted at Animal Husbandry Biology Laboratory, Departement of Animal Husbandry, Faculty of Agriculture, University of North Sumatera for 4 weeks from November until December 2016. This research used completely randomized design (CRD) factorial with 9 combined treatment and 3 replication. The treatment consists of A0B0, A0B1, A0B2, A1B0, A1B1, A1B2, A2B0, A2B1, A2B2. The observed parameters were cutting weight, carcass weight, and carcass percentage. The result showed that the average weight of broiler chicken ranged from 1829,50 – 1929,50 gram/head. The average of Carcass weight ranged from1424,75 – 1676,50 gram/head. And the average of carcass percentage ranged from 78,01 % - 87,98 %. This research conlude that the best combination is A1 and B0.